The prognostic value of gastrointestinal bleeding in gastrointestinal stromal tumor: A propensity score matching analysis - Wenze Wan; Zhen Xiong; Xiangyu Zeng; Wenchang Yang; Chengguo Li; Yu Tang; Yao Lin; Jinbo Gao; Peng Zhang; Kaixiong Tao (Cancer Medicine, 2019)
Abstract Background and objectives Whether gastrointestinal (GI) bleeding indicates gastrointestinal stromal tumor (GIST) rupture and impacts prognosis is unclear. We examined the prognostic value of GI bleeding in GIST. Methods Primary GIST patients with (GB group) or without (NGB group) initial symptoms of GI bleeding were retrospectively studied. Propensity score matching (PSM) was conducted to reduce confounders. Results Eight hundred patients were enrolled. Male gender [odds ratio (OR) = 1.517, P = 0.011], tumors in the small intestine (OR = 2.539, P < 0.001), and tumor size 5‐10 cm (OR = 2.298, P = 0.004) increased the odds of GI bleeding; age >60 years decreased the odds (OR = 0.683, P = 0.031). After PSM, 444 patients were included (222 in each group). Relapse‐free survival (RFS) (P = 0.001) and overall survival (OS) (P = 0.002) were both superior in the GB group. In subgroup analysis, the GB group achieved a superior RFS (P = 0.005) and OS (P = 0.007) in patients with small intestine GIST, but not stomach or colorectal GIST. Conclusions GIST patients with age <60, male gender, tumors located in the small intestine, and tumors 5‐10 cm in size had a higher risk of GI bleeding. GIST patients with GI bleeding had a superior RFS and OS. This difference was statistically significant only in small intestine GIST.